2015
DOI: 10.1155/2015/279192
|View full text |Cite
|
Sign up to set email alerts
|

Short Duration Combined Mild Hypothermia Improves Resuscitation Outcomes in a Porcine Model of Prolonged Cardiac Arrest

Abstract: Objective. In this study, our aim was to investigate the effects of combined hypothermia with short duration maintenance on the resuscitation outcomes in a porcine model of ventricular fibrillation (VF). Methods. Fourteen porcine models were electrically induced with VF and untreated for 11 mins. All animals were successfully resuscitated manually and then randomized into two groups: combined mild hypothermia (CH group) and normothermia group (NT group). A combined hypothermia of ice cold saline infusion and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A similar study found that 7/7 (100%) pigs fully recovered if they were cooled to 32–34°C within 2 hours of return of spontaneous circulation (ROSC) and maintained in that range for 4 hours (Yu et al , 2015). Only 3/7 (43%) control animals that were maintained at normothermia in this study survived 4 days.…”
Section: Introductionmentioning
confidence: 95%
“…A similar study found that 7/7 (100%) pigs fully recovered if they were cooled to 32–34°C within 2 hours of return of spontaneous circulation (ROSC) and maintained in that range for 4 hours (Yu et al , 2015). Only 3/7 (43%) control animals that were maintained at normothermia in this study survived 4 days.…”
Section: Introductionmentioning
confidence: 95%
“…From the physiological point of view, brain temperature should be the priority monitoring site for survivors with TTM. With the fact that the jugular bulb blood is derived from intracerebral vasculature, the jugular vein temperature has been considered as an accurate index of cerebral cortical temperature in various studies [ 8 , 9 ]. However, both brain cortex and jugular vein temperature are not so easily detected and insufficient data of temperature value may lead to delay initiation and insufficient or excessive TTM.…”
Section: Discussionmentioning
confidence: 99%
“…The ventricular fibrillation ECG data were retrospectively collected from previous studies on mild hypothermia improving CPR in a porcine model. [ 19 ] ECG and blood pressure waveform signals were collected with a Windaq hardware‐/software‐supported data acquisition system (Dataq Instruments Inc., Akron, OH, USA), with a data sampling rate of 300 Hz. The data included the initiation of a model of ventricular fibrillation, the initiation of chest compressions for CPR, and the recovery from successful defibrillation to self‐circulation or the failure of resuscitation.…”
Section: Methodsmentioning
confidence: 99%